2010
DOI: 10.1007/s11769-010-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant types on physico-chemical properties of reclaimed mining soil in Inner Mongolia, China

Abstract: A field experiment was conducted in Jungar Banner, Inner Mongolia, China to study the effects of plant types on the physical structure and chemical properties of open-cast mining soils reclaimed for 15 years, and to analyze the triggering factors of the soil formation. Results indicate that plant types affect soil-forming process especially in the upper layer (0-20 cm), and the spatial structure of reclaimed plant is the main reason for variability of the soil-forming process. In the upper soil layer at the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Different tree species have varying degree of ameliorative affect on mine soils (Mukhopadhyay and Maiti, 2011;Juwarkar et al, 2010;Mendes Filho et al, 2010;Sinha et al, 2009;Dutta and Agrawal, 2003). Yao et al (2010) studied the improvement in physicochemical properties of a 15-year old reclaimed coal mine soils (Inner Mongolia, China) and concluded that different tree species have varying degree of influence on soil forming process. Dutta and Agrawal (2001) also reported significant difference in improvement of physico-chemical properties by five exotic tree species planted in the mine soils (Jayant opencast project, Madhya Pradesh, India).…”
Section: Introductionmentioning
confidence: 99%
“…Different tree species have varying degree of ameliorative affect on mine soils (Mukhopadhyay and Maiti, 2011;Juwarkar et al, 2010;Mendes Filho et al, 2010;Sinha et al, 2009;Dutta and Agrawal, 2003). Yao et al (2010) studied the improvement in physicochemical properties of a 15-year old reclaimed coal mine soils (Inner Mongolia, China) and concluded that different tree species have varying degree of influence on soil forming process. Dutta and Agrawal (2001) also reported significant difference in improvement of physico-chemical properties by five exotic tree species planted in the mine soils (Jayant opencast project, Madhya Pradesh, India).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s on the Chinese Loess Plateau, production and construction activities, such as coal mining, mineral mining, and expressway construction, have altered landforms, removed vegetation, and excavated a large amount of surface material, which is deposited in heaps (Fu, Lin, Ma, & Zhu, 2010; Guo et al, 2020; Zhang, Gao, Yang, Li, & Tian, 2015). Due to their loose structure, these abandoned spoil heaps have caused considerable soil erosion (Wang et al, 2012), which has resulted in land degradation and severely damaged the ecology and environment (Luo, Xie, & Lv, 2019; Zhang, Gao, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the rainy season, FSPs are clearly associated with improved plant survival (Tianjiao et al, 2018). In addition, FSPs can improve soil organic matter and enhance land productivity (Fu, Lin, et al, 2010). Han et al (2018) also found that compared with bare land, land with FSPs reduce runoff and sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Revegetation, a common method adopted by many countries such as USA, China and India, has been proved to be a proper reclamation way to accelerate the soil-forming processes, build up soil organic matter, develop nutrient cycling and restore soil productivity [ 8 , 9 ]. According to Fu [ 10 ], physico-chemical properties of mine soil in Inner Mongolia of China have improved a lot after 15-year reclamation. However, not all trees are of the same efficiency.…”
Section: Introductionmentioning
confidence: 99%